PELATIHAN WIRAUSAHA PETANI MUDA MELALUI BUDIDAYA HIDROPONIK SISTEM WICK DAN NFT UNTUK MENDUKUNG PEMBANGUNAN DESA BERKELANJUTAN BERBASIS POTENSI DESA - Puspaningrum, Diah; Putri, Widya Kristiyanti; Aji, Joni Murti Mulyo; Subekti, Sri; Novikarumsari, Nurul Dwi; Patricia, Susan Barbara (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Universitas Abdurachman Saleh Situbondo, 2024)
Suci Village, Panti District, is one of the villages fostered by Jember University which has very good agricultural potential. The young generation of the village needs to be given education and mentoring to become more familiar with the concept of modern agriculture and realize it in cultivation and entrepreneurship practices. The community service in Suci Village aims to train the Karang Taruna